Knowledge management in Iran - Ebrahim, Nader Ale; Ghazizadeh, Ali; Golnam, Arash (2006)
In the highly competitive global market, only organizations survive in which, knowledge has replaced labor and natural resources as the key source of sustainable growth and development.The organizations that have learn doing things differently and doing different things. In such organizations knowledge and learning are widely considered as sustainable sources of competitive advantage.In this paper first we take a look at the history and the pioneers of knowledge management in Iran analyzing the evolutionary trend of knowledge management and its current condition in Iran. Then we trace the emphasis put on knowledge management in the fourth economic, social and cultural development plan proposed by the Iranian Government with an analytical approach.Next but still important we present the summary of the 5th Seminar of the Industries and Mines Research and Development Centers by the name of Research and Development and Knowledge Management which was held on 23 and 24 th of Nov. 05 in Tehran by The R&D Society of Iranian Industries and Mines with the help of the Deputy Office for Planning, Research & Development of the Ministry of Industries & Mines and the Deputy Office of Research of the Ministry of Science, Research & Technology.Since we were directly involved in the above mentioned seminar from both scientific and executive point of view we believe this seminar is the most up to date case study about knowledge management in Iran.